Wacana Paham Keagamaan TV One dan Metro TV dalam Pemberitaan Demo 411 di Jakarta - Muhammad Ridwan; Musta'in Musta'in (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2017)
In 2016 there was a massive religious demonstration in Jakarta involving several Islamic groups. The rally was triggered by the statements from Jakarta’s governor candidate Basuki Tjahaya Purnama (Ahok) at Kepulauan seribu which interpreted by some as a blasphemy against Islam. The protest which conducted on November was considered as the biggest in 2016. At that time most of media, including TV One and Metro TV were highlited this event which estimated attended by hundreds million of protesters. With this case of reports, this writing tries to formulate this following issues: How is the relious discourse broadcasted by TV One and Metro TV towards 411 demonstration. Using Teun Van Dijk’s discourse theory, this study is a qualitative research. News that was analyzed were 6 news with the details of 3 from Metro TV and 3 from TV One. Discourse analysis in this case is used as a tool to examine discourse on both televisions. There are three stages which are texts analysis, cognitive analysis and social analysis. Results of this study show that TV One’s discourse towards the rally is that Islamic organization whose on the rally is a tolerance group, whose maintaining unity and practicing Islamic shariaa. Meanwhile, according to Metro TV is that the organization is more on a hardline ideology, non tolerance and promoting violence.